3D‐Printing of High‐κ Thiol‐Ene Resins with Spiro‐Orthoesters as Anti‐Shrinkage Additive. Issue 12 (14th October 2019) - Marx, Philipp; Romano, Angelo; Roppolo, Ignazio; Chemelli, Angela; Mühlbacher, Inge; Kern, Wolfgang; Chaudhary, Sunny; Andritsch, Thomas; Sangermano, Marco; Wiesbrock, Frank
Abstract: Tri(ethylene glycol) divinyl ether and the spiro‐orthoester 2‐((allyloxy)methy)‐1, 4, 6‐trioxospiro[4.4]nonane can be formulated in different ratios and crosslinked by thiol‐ene reactions. The spiro‐orthoester is used as anti‐shrinkage additive, enabling shrinkage reduction of up to 39%. Addition of a radical photoinitiator for the thiol‐ene reaction and a cationic photoinitiator for the double ring‐opening of the spiro‐orthoester enables dual‐curing for application in 3D‐printing. The formulation free of the spiro‐orthoester shows gelation during the printing process and, correspondingly, low resolution. The formulations containing the spiro‐orthoester exhibit higher resolutions in the range of 50 µm. The resins containing mixtures of tri(ethylene glycol) divinyl ether and the spiro‐orthoester show permittivities as high as 10 4 . The dielectric loss factor of the resins is in the range of 0.5–7.6, and the conductivity in the range of 1.3⋅10 −11 to 2.0⋅10 −11 S cm −1 . These high‐κ materials can be 3D‐printed by digital light processing for the next generation of electronic materials. Abstract : The shrinkage of tri(ethylene glycol) divinyl ether‐based thiol‐ene resins is reduced by 39% using bicyclic spiro‐orthoesters as anti‐shrinkage additive. A dual‐cure mechanism enables 3D‐printing of the resin formulations by digital light processing with resolutions in the range of 50 µm. The high permittivity enables potential applications as high‐κ material.